The effect of chemotherapy in patients with stage I mucinous ovarian cancer undergoing fertility-sparing surgery - Long, Xingtao; Li, Rengui; Tang, Ying; Yang, Lingling; Zou, Dongling (Frontiers in Oncology, 2022)
Objective To determine the effect of adjuvant chemotherapy in patients with stage I mucinous ovarian cancer (MOC) undergoing fertility-preserving surgery. Patients and methods The clinicopathological characteristics and survival information of young women with stage I MOC from SEER databases between 2004 and 2019 were collected. The relationship between chemotherapy and the characteristics was examined by univariate and multivariate logistic regression analyses. Univariable and multivariate Cox proportional hazards survival analysis were employed for cancer-specific survival. Cox analysis was performed to build a nomogram model. Results All 901 eligible patients with stage I MOC were screened from the SEER database. There were 321(35.6%) patients aged 9-30 years, 580(64.4%) aged 31-45 years, 645 (71.6%) patients with stage IA/IB, 256 (28.4%) with stage IC disease, 411(45.6%) who underwent fertility-sparing surgery, and276(30.6%) who received postoperative adjuvant chemotherapy. Multivariate logistic regression analyses showed that postoperative chemotherapy was often used in patients aged 31-45 relative to aged 9-30 (HR: 2.215, 95%CI 1.443-3.401, P < 0.001) or with grade 3 compared to grade 1 tumors (HR: 7.382, 95%CI 4.054-13.443, P < 0.001) or with stage IC compared to stage IA/IB (HR: 6.436, 95%CI 4.515-9.175, P < 0.001) or with non-fertility sparing surgery relative to fertility-sparing (HR:2.226, 95%CI 1.490-3.327, P < 0.001). Multivariate analysis for the special population with fertility preservation indicated that patients with chemotherapy (HR: 2.905, 95% CI: 0.938-6.030, P=0.068) or with grade 3 (HR: 4.750, 95% CI: 1.419-15.896, P=0.011) had a greater risk of mortality. Significant CSS differences were observed between the non-chemotherapy and chemotherapy groups in MOC when patients were stage IA/IB-grade 2 (P=0.004) (10-year CSS rates of chemotherapy=84%, non-chemotherapy = 100%), but not when they were stage IA/IB-grade 1, stage IA/IB-grade 3 or stage IC (both P>0.05). A prognostic prediction nomogram model was built for stage I MOC patient who underwent fertility-sparing and the C-index was 0.709. Discussion The patients aged 31-45 years, with grade 3, stage IC, and non-fertility-sparing surgery were more likely to receive adjuvant chemotherapy in the real world. For stage I MOC patient who underwent fertility-sparing surgery, the choice of chemotherapy may increase the risk of death, and it should be carefully selected in clinical practice.